THE EVALUATION OF INVESTIGATOR’S INVESTIGATION REPORTS USING APPRAISAL FRAMEWORK - Panggabean, Sarma; Surbakti, Ernawati Br; Octaviana, Yessy; Gusar, Martua Reynhat Sitanggang (Curricula: Journal of Teaching and Learning, 2026)
Legal discourse, specifically Investigation Reports (Berita Acara Pemeriksaan/BAP), serves as a critical evidentiary foundation in the criminal justice system. Ideally, these documents must embody strict neutrality and objectivity to ensure fair legal proceedings. However, a significant research problem persists: the potential infiltration of subjective evaluative language that may compromise legal clarity, fairness, and procedural justice. Despite their profound legal weight, there is limited empirical understanding of how linguistic appraisal mechanisms operate within various BAP types. Unchecked evaluative language risks introducing bias, manipulating narrative perspectives, and creating legal ambiguities that could adversely affect suspect rights and judicial outcomes. This gap necessitates a critical linguistic examination to uncover hidden subjectivities within ostensibly objective legal texts. Consequently, this study aims to evaluate the language used in Investigation Reports by applying Appraisal Theory to analyze Attitude and Positioning patterns. This research employed a qualitative descriptive design supported by corpus analysis using the Simple Concordance Program (SCP). The data consisted of eight types of Investigation Reports obtained from the Galang Sub-district Police Station. The analysis focused on identifying evaluative lexical items and their distribution across report types. To ensure analytical reliability, appraisal categories were classified based on predefined criteria, and cross-checking was conducted to reduce subjectivity. The findings indicate that negative Attitude dominates the Suspect Investigation Reports (35.7%), while negative Positioning is most prominent in Confiscation Reports (24.2%). In general, Suspect Reports show the highest frequency of appraisal usage (97.99%), suggesting a high degree of evaluative language in representing events. These findings highlight the importance of linguistic awareness in drafting investigation reports, particularly in maintaining neutrality and clarity to avoid potential misinterpretation. The prevalence of negative appraisal suggests an inherent bias that could influence judicial outcomes, underscoring the urgent need for standardized linguistic protocols in legal documentation to uphold justice and procedural integrity